IMPLEMENTASI MODEL PEMBELAJARAN APTITUDE TREATMENT INTERACTION DALAM MENINGKATKAN KEGIATAN BELAJAR DAN PRESTASI BELAJAR SISWA - Eko Nursalim; Ramdanil Mubarok (Al-Rabwah, 2023)
This studys' purpose was to analyze the application of the ATI learning model in improving learning activities and student learning outcomes in Al-Qur'an Hadith subjects. The method used in this research is classroom action research. As the result of the application of the ATI learning model can improve the learning activities of Madrasah Aliyah Nurul Hikmah Sangatta students. Thus could be proven by an increase in the percentage of student learning activities in cycle one by 78%. In the same in the next cycle, there was an increase of 88%. Furthermore, the implementation of the ATI learning model can also improve student achievement in the Qur'an Hadith subjects at Madrasah Aliyah Nurul Hikmah Sangatta where student learning completeness has an increase in the percentage in the first cycle of 82.5, as well as in the next cycle, there is an increase of 98%